2009
DOI: 10.4052/tigg.21.23
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of inverting glycoside hydrolases into catalysts for synthesizing glycosides employing a glycosynthase strategy

Abstract: 23Trends in Glycoscience and Glycotechnology Vol. 21 No. 117 (2009) AbstractReducing-end xylose-releasing exo-oligoxylanase (Rex, EC. 3.2.1.156) is an inverting xylanolytic enzyme, belonging to the glycoside hydrolase (GH) family 8, which hydrolyzes xylooligosaccharides to release xylose (X1) from its reducing end. Rex hydrolyzes a-xylobiosyl ‰uo-ride (a-X2F) to yield xylobiose (X2) only in the presence of X1, conˆrming the Hehre resynthesis-hydrolysis mechanism. A library of mutant Rex at the catalytic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Three classes of enzymes are employed for carbohydrate synthesis: GTases, exo -glycosidases, and endo -glycosidases. Additionally, these classes of enzymes have been enhanced over the past decade through genetic engineering to form mutant enzyme classes, such as glycosynthases and thioglycoligases, which are designed or selected for increased yields, enzyme stability, and improved donor and acceptor specificity. ,, Enzymes can also be exploited in the glycoengineering of cells (see section 5).…”
Section: Chemoenzymatic Synthesis Elaboration and Remodeling Of Carbo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Three classes of enzymes are employed for carbohydrate synthesis: GTases, exo -glycosidases, and endo -glycosidases. Additionally, these classes of enzymes have been enhanced over the past decade through genetic engineering to form mutant enzyme classes, such as glycosynthases and thioglycoligases, which are designed or selected for increased yields, enzyme stability, and improved donor and acceptor specificity. ,, Enzymes can also be exploited in the glycoengineering of cells (see section 5).…”
Section: Chemoenzymatic Synthesis Elaboration and Remodeling Of Carbo...mentioning
confidence: 99%
“…Detailed accounts of evolving and applying glycosynthases have been provided by Withers and co-workers. ,,,, Notably, this mechanism-based engineering technique has been expanded to create novel thioglycosynthases . Glycosynthases have also been more recently generated from the inverting glycosidases, including exo -β-oligoxylanase , and 1,2-α-fucosidase, , expanding the types of glycosidases that can be engineered for synthetic ends. Undoubtedly, engineering new glycosynthases will continue to create useful enzymes for glycan synthesis, and the current success of the technique is underscored by the variety of enzymes that are available to enact various stereo- and regiochemical linkages, as summarized in Table . , …”
Section: Chemoenzymatic Synthesis Elaboration and Remodeling Of Carbo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have shown that inverting glycosidases may be converted into glycosynthases . Glycosynthases are engineered glycoside hydrolases that catalyze the synthesis of glycosides from activated donors, such as glycosyl fluorides or glycosyl azides . A GH8 enzyme, reducing‐end xylose‐releasing exo‐oligoxylanase from Bacillus halodurans ( Bh Rex), is an inverting glycosidase that has the (α/α) 6 barrel fold and may be converted to a glycosynthase .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the group of Wada et al has reported that some mutants of GH95 1,2-α-L-fucosidase showed 1,2-α-Lfucosynthase activity (46), suggesting that enzymes of families GH15, GH37, GH63, and related enzymes can be converted into glycosynthases by means of mutagenesis (51,52). Further studies may provide information on the industrial application of these enzymes.…”
Section: E Concluding Remarksmentioning
confidence: 99%